Peran Guru Bidang Studi dalam Menanamkan Pendidikan Karakter Pada Siswa Kelas XI Di SMA HKBP Sidorame Medan Tahun 2025 - Sibarani, Anastasiah; Siregar, Nurliani; Pardede, Lukman; Simanjuntak, Hotmaida (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
Teachers who are run in relation to character education in students researchers found that students who often come late, students who do not use school attributes, are not neatly dressed, students who do not maintain cleanliness, students who throw garbage in the wrong place. This study aims to determine the role of subject teachers in instilling character education in class XI students at SMA HKBP Sidorame Medan in 2025 and to determine the factors that influence the success of instilling character education in SMA HKBP Sidorame Medan. The research method used is qualitative. Data collection techniques using interview techniques, questionnaires and documentation, then data analysis techniques using the Miles and Huberman model, namely data reduction, data presentation and verification or drawing conclusions. Based on research conducted by interviews and questionnaires that the role of class teachers in instilling character education in class XI students of SMA HKBP Sidorame Medan "Good" The results of the questionnaire that the author obtained in this study 62.00% are in the interval 61 - 80%.